Influence of the Mixing Ratio on the Dynamics of Polymer Segments in Polyelectrolyte Complexes. Issue 7 (1st March 2021) - Lappan, Uwe; Naas, Carolin; Scheler, Ulrich
Abstract: The rotational dynamics of the spin‐labeled polyacid poly(ethylene‐ alt ‐maleic acid) (P(E‐ alt ‐MA)) in polyelectrolyte complexes (PECs) formed with the polycations poly(allylamine hydrochloride) (PAH) and poly(diallyldimethylammonium chloride) (PDADMAC) are studied by electron paramagnetic resonance (EPR) spectroscopy as a function of the mixing ratio of polycation and polyanion. At low mixing ratios a superposition of two spectral components is found. The fast‐motion component observed arises from chain segments of the polyacid in excess, which form a stabilizing shell around the PEC particles. The other one is a slow‐motion component, which is caused by the interaction of charged chain segments of the polyacid with the oppositely charged segments of the polycation in the core. At high mixing ratios, the spectra are dominated by the slow‐motion component, because the polyacid is exclusively located in the core. The study has shown that the outer extrema separation of the slow‐motion component decreases with increasing mixing ratio, i.e., the rotational mobility of the polyacid segments in the core increases when the excess of the polycation becomes larger. An increasing number of extrinsic polycation sites within the core of the PECs which reduces the density of intrinsic binding sites are assumed to be the reason. Abstract : Oppositely charged polyelectrolytes form polyelectrolyte complexes (PECs) in a self‐assembly process when aqueous solutions of these polymers are mixed. The dynamics of PECs composed of the polyacid poly(ethylene‐ alt ‐maleic acid) P(E‐ alt ‐MA) and oppositely charged polycations are studied as a function of the mixing ratio by electron paramagnetic resonance (EPR) spectroscopy using spin‐labeled polyacid as a reporter molecule.